Extract from palm leaves and a method for producing the same - Mohamed, Suhaila; Jafri, Juliana; Mohamed Mustapha, Noordin; Ahmad, Intan Natasya; Abdul Razak, Mursyida (2007)
A method for preparing an herbal extract comprises the steps of pre-treating foliages derives from a plant of Arecaceae family: extracting the pre-treated foliages by using a polar solvent: removing the pre-treated foliages from the used polar solvent; and concentrating the used polar solvent to acquire the herbal extract.